1983
DOI: 10.1007/bf01965185
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical response of alkaline phosphatase activity during the healing of cutaneous wounds in a cat-fish

Abstract: Summary. The activity of alkaline phosphatase in the various tissue components of the regenerating skin of a cat-fish has been studied. A marked increase in alkaline phosphatase activity in the cells of migrating epithelium has been correlated with their highly active state. High alkaline phosphatase in the basal cells after 2 days has been found to have played an important role in cell multiplication and differentiation. The functional significance of this enzyme is discussed in relation to the granulation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
12
1
Order By: Relevance
“…In teleost fish, it is known that, in addition to macrophages, epidermal cells show phagocytotic responses and produce peroxidase and acid phosphatase (Espenes et al 1997;Iger and Abraham 1990;Phromsuthirak 1977;Press et al 1994). Alkaline phosphatase activity was also detected in phagocytotic cells during wound healing in catfish and carp, although no peroxidase activity was detected under normal circumstances (Iger and Abraham 1990;Rai and Mittal 1983). In the present study, apoptotic bodies of melanophores, which seemed to be engulfed by phagocytotic cells, showed endogenous activities of peroxidase and acid phosphatase but not of alkaline phosphatase.…”
Section: Apoptosis In Pigment Cellscontrasting
confidence: 43%
“…In teleost fish, it is known that, in addition to macrophages, epidermal cells show phagocytotic responses and produce peroxidase and acid phosphatase (Espenes et al 1997;Iger and Abraham 1990;Phromsuthirak 1977;Press et al 1994). Alkaline phosphatase activity was also detected in phagocytotic cells during wound healing in catfish and carp, although no peroxidase activity was detected under normal circumstances (Iger and Abraham 1990;Rai and Mittal 1983). In the present study, apoptotic bodies of melanophores, which seemed to be engulfed by phagocytotic cells, showed endogenous activities of peroxidase and acid phosphatase but not of alkaline phosphatase.…”
Section: Apoptosis In Pigment Cellscontrasting
confidence: 43%
“…As it was indicated previously for lysozyme, significant differences in the specific activities of these enzymes were observed among specimens [119]. Increased activities of phosphatases were demonstrated in epidermal cells during skin regeneration related to cutaneous wound healing in the catfish (Heteropneustes fossilis) 6 ISRN Immunology [126][127][128] and in Atlantic salmon mucus during parasitic infections or stress [25,129] and were considered to play a protective role in the initial stage of wound healing in the common carp (Cyprinus carpio) [128,130]. Furthermore, alkaline phosphatase has been demonstrated as a potential stress indicator in skin mucus of Atlantic salmon [129].…”
Section: Enzymesmentioning
confidence: 72%
“…Furthermore, Schmidt and Weary (1962) observed an increase in epidermal AP throughout limb regeneration in the newt Diemictylus viridescens. Rai and Mittal (1983) observed a marked increase in AP activity in the migrating cells of the epithelium during cutaneous wound-healing in the catfish Heteropneustesfossilis, which correlated with their highly active state. They also suggested that high AP activity in basal cells is important in cell multiplication and differentiation.…”
Section: Discussionmentioning
confidence: 84%
“…Possible functions of AP in vertebrate mineralization include increasing local concentrations of inorganic phosphate (Pi), local destruction of mineral crystal growth-inhibitors, acting as Pi-transporter, acting as a Ca 2 +-binding protein, acting as a Ca 2 + pump in cell membranes, or indirectly acting in mineralization as a regulator of cell division and differentiation (see Wuthier and Register * Please address all correspondence to Dr. J. E. Donachy at her present address: Department of Biological Sciences, University of South Alabama, Mobile, Alabama 36688, USA 1985 for review). In addition to mineralization, this enzyme has also been correlated with the process of regeneration and cell differentiation during limb regeneration (Karczmar andBerg 1951, Schmidt andWeary 1962) and during cutaneous wound-healing in vertebrates (Rai and Mittal 1983).…”
Section: Introductionmentioning
confidence: 99%